IMAGINARY PARLIAMENTS: EXCAVATING THE METAPHOR OF CONSENSUS WITHIN BLOCKCHAIN TECHNOLOGIES - Jankowski, Steve J. (AoIR Selected Papers of Internet Research, 2023)
Blockchain technologies function partly according to consensus algorithms and protocols. Beyond a practical means of allowing these technologies to function, they can also be considered to have imagined affordances that “emerge between users’ perceptions, attitudes, and expectations; between the materiality and functionality of technologies; and between the intentions and perceptions of designers” (Nagy and Neff, 2015, p. 5). In the case of blockchains, these affordances are attached to representing social trust and decentralizing electoral processes. As such, blockchain technologies have been intimately woven into discourses that imagine the future of governance, transparency, and democratic decision-making.But how has this happened? In this paper I identify that at the root of these discourses is the ambiguous concept of "consensus" and that socio-political meanings of consensus have be re-written as a set of technical operations. Through a combination of metaphor analysis and content analysis of canonical computer science papers and news articles, I demonstrate how the oscillation between technical and political meanings became the basis of the celebratory discourses around blockchain technologies. Through this analysis I demonstrate how computer scientists used a metaphor to guide technical development, and then this metaphor took on a foundational aspect of the socio-political value of the technology in the form of visions for decentralization, autonomy, and democracy.